Towards Dual‐Functionality Spin‐Crossover Complexes. Issue 7 (26th January 2018) - Feltham, Humphrey L. C.; Dankhoff, Katja; Meledandri, Carla J.; Brooker, Sally
Abstract: The multistep synthesis of a versatile new 4‐substituted 3, 5‐bis(2‐pyridyl)‐1, 2, 4‐triazole (Rdpt ) ligand, 4‐[4‐(2‐aminomethyl)phenyl]‐3, 5‐bis(2‐pyridyl)‐4  H ‐1, 2, 4‐triazole (apdpt ), is reported, which features a reactive aminomethyl para ‐substituent on the phenyl group that points "out of the back" of the triazole. This enables further functionalisation under mild conditions by using a range of esters to form an amide link. Specifically, this proof of principle study demonstrates the synthesis ofapdpt successfully appended with gold‐binding thioctic acid (tpdpt ), graphene‐binding/emissive pyrene/propylpyrene (prdpt /pbdpt ), and a Langmuir–Blodgett film‐forming polyethylene glycol (PEG) tail (pgdpt ). These ligands are subsequently reacted with [Fe(pyridine)4 (NCBH3 )2 ] to give the mononuclear iron(II) complexes [Fe(Rdpt )2 (NCBH3 )2 ]⋅ solvent, in whichRdpt /solvent istpdpt /2.5 H2 O (1 ), prdpt /0.5 CHCl3 ⋅ H2 O (2 ), andpbdpt /0.5 CHCl3 ⋅ 2 H2 O  (3 ), as red powders. Magnetic studies on these powders indicate that the complexes undergo only very gradual and incomplete spin crossover, from completely or mostly high spin at 300 K, to half or three‐quarters high spin at 50 K. Gold nanoparticles are successfully functionalised with the thioctic acidtpdpt ligand to givetpdpt @Au with an average diameter (as determined by TEM) of (3.1±0.7) nm. Preliminary studies on the two pyrene systems in dimethylformamide show that upon excitation at λ =345 nm the blue fluorescence observed for the free ligands is retained, essentially unaffected, in the respective complexes. Abstract : Ripe for development : The versatile new 4‐substituted 3, 5‐bis(2‐pyridyl)‐1, 2, 4‐triazole (Rdpt )‐type ligand 4‐[4‐(2‐ aminomethyl )phenyl]‐3, 5‐bis(2‐pyridyl)‐4  H ‐1, 2, 4‐triazole (apdpt ) undergoes further functionalisation under mild conditions to add a wide range of additional properties (see scheme), for the future generation of dual‐functionality iron(II) spin‐crossover‐active complexes).